2023
DOI: 10.3390/electronics13010180
|View full text |Cite
|
Sign up to set email alerts
|

A Hardware-Simplified Soft-Start Scheme for Current-Fed Full-Bridge DC-DC Converter

Shupeng Li,
Zhenbin Li,
Weiqi Meng
et al.

Abstract: At present, the current-fed full-bridge DC-DC converter still faces two inherent defects, namely, the soft-start issue during the start-up process and the voltage spike issue in normal working conditions. In existing research, a large number of attempts have been reported to overcome these two inherent issues. However, the existing solutions are all based on both redundant soft-start circuits and snubber circuits, and two different circuits are required. As a result, the cost of the current-fed full-bridge DC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was concluded that employing a voltage-fed full-bridge on the low side neither proves cost-effective nor efficient. In another study referenced as 18 , the current-fed converter was positioned on the low side while the voltage-fed converter was positioned on the high side. To maximize efficiency, careful consideration must be given to selecting the active clamp capacitor tailored precisely to the application at hand.…”
Section: Grid Voltage and Converter Topology Selectionmentioning
confidence: 99%
“…It was concluded that employing a voltage-fed full-bridge on the low side neither proves cost-effective nor efficient. In another study referenced as 18 , the current-fed converter was positioned on the low side while the voltage-fed converter was positioned on the high side. To maximize efficiency, careful consideration must be given to selecting the active clamp capacitor tailored precisely to the application at hand.…”
Section: Grid Voltage and Converter Topology Selectionmentioning
confidence: 99%